The peacock and the sparrow : a novel - Berry, I. S. (Atria Books, 2023)
Shane Collins, a world-weary CIA spy, is ready to come in from the cold. Stationed in Bahrain off the coast of Saudi Arabia for his final tour, he's anxious to dispense with his mission, uncovering Iranian support for the insurgency against the monarchy. But then he meets Almaisa, a beautiful and enigmatic artist, and his eyes are opened to a side of Bahrain most expats never experience. When his trusted informant becomes involved with a murder, Collins finds his growing romance with Almaisa and Bahrain upended. In an instant he's caught in the crosshairs of a revolution. Now he must rely on his skills to navigate a bloody uprising, win Almaisa's love, and uncover the blurred lines between the dark secrets of both Bahrain and the United States.